PENERAPAN SUPERVISI MANAJERIAL UNTUK MENINGKATKAN KINERJA KEPALA SEKOLAH DALAM MENYUSUN PROGRAM KERJA SEKOLAH DI SMP NEGERI 6 SABANG - YULI FERI SHINTA (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2021)
This study aims to determine the improvement of the principal's performance in preparing school work programs at SMP Negeri 6 Sabang through managerial supervision. This research technique is School Action Research (PTS) which consists of 2 cycles, each cycle consists of 4 (four) stages, namely planning, implementation, observation and reflection. The subjects in this study were the principal and the school development team of SMP Negeri 6 Sabang. As for the research results obtained, through the application of managerial supervision has been able to improve the performance of school principals in preparing school work programs. This is known from the final score obtained from the school work program planning instrument. At the end of the pre-cycle the score obtained was 42.5 under category and D predicate. For this reason, coaching and mentoring was carried out so that in cycle I and cycle II the principal and the school development team understood each component of the school work program planning instrument. In the first cycle the final score was 62.5 sufficient category and predicate C. There was an increase in the value of 20 from the pre-cycle to the first cycle. At the end of the second cycle the score was 80 good categories and B predicate. An increase in the value of 18.5 from the first cycle to cycle II. So it can be concluded that the principal and the school development team who are the subjects in this study have performed well in compiling school work programs with good results. ABSTRAKPenelitian ini bertujuan untuk mengetahui peningkatan kinerja kepala sekolah dalam menyusun program kerja sekolah di SMP Negeri 6 Sabang melalui supervisi manajerial. Teknik penelitian ini adalah Penelitian Tindakan Sekolah (PTS) yang terdiri dari 2 siklus, setiap siklus terdiri 4 (empat) tahapan yaitu perencanaan, pelaksanaan, pengamatan dan refleksi. Subyek dalam penelitian ini adalah kepala sekolah dan tim pengembang sekolah SMP Negeri 6 Sabang. Adapun dari hasil penelitian diperoleh, melalui penerapan supervisi manajerial telah dapat meningkatkan kinerja kepala sekolah dalam menyusun program kerja sekolah. Hal ini diketahui dari nilai akhir yang didapat dari instrumen perencanaan program kerja kerja sekolah. Pada akhir pra siklus nilai yang diperoleh sebesar 42,5 katagori kurang dan predikat D. Untuk itu dilakukan pembinaan dan pembimbingan sehingga pada siklus I dan siklus II kepala sekolah dan tim pengembang sekolah memahami setiap komponen pada instrumen perencanaan program kerja sekolah. Pada siklus I nilai akhir adalah 62,5 katagori cukup dan predikat C. Terjadi peningkatan nilai sebesar 20 dari pra siklus ke siklus I. Pada akhir siklus II diperoleh nilai adalah 80 katagori baik dan predikat B. Peningkatan nilai sebesar 18,5 dari siklus I ke siklus II. Sehingga dapat disimpulkan kepala sekolah dan tim pengembang sekolah yang menjadi subjek dalam penelitian ini telah memiliki kinerja dalam menyusun program kerja sekolah dengan hasil baik.